ON THE ROLE OF KI-67 AND P53 PROLIFERATION MARKERS IN PATIENTS WITH RECURRENT MACRO AND GIANT INACTIVE PITUITARY TUMORS - Миртухтаева М. Б.; Худайбергенов Ш. А.; Урманова Ю. М. (American Journals Publishing, 2024)
The aim of the study was to study the prognostic value of the proliferation markers Ki-67 and p53 in patients with recurrent macro and giant inactive pituitary adenomas.
Keywords: NGA, immunohistochemical research, Ki-67, p53